If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w = 2w + 30 Reorder the terms: w = 30 + 2w Solving w = 30 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. w + -2w = 30 + 2w + -2w Combine like terms: w + -2w = -1w -1w = 30 + 2w + -2w Combine like terms: 2w + -2w = 0 -1w = 30 + 0 -1w = 30 Divide each side by '-1'. w = -30 Simplifying w = -30
| 10t-81=9t-71 | | 6t-80=t | | u-32=2u-93 | | 2u-72=u-28 | | 10v+1=9v+3 | | 6x^2*tgx= | | 3n+16=37 | | 16f+27=18f+7 | | 6A-7=17 | | 0.01x-0.7x+0.09x+0.3x= | | 8x=153-9x | | 6-9x=0 | | X+3x=359 | | 5.59=-0.2877x+13.721 | | 5.59=0.2877x+13.721 | | 4.02=-0.2877x+13.721 | | 25-55+(85+65)=5x | | 4.02=-8262ln(X)+33.124 | | -29.104=-8.262ln(X) | | 16y=83 | | 5*4*3*2*1=1 | | 6+3b=-16 | | 3x-1=4-2x | | 4-4(1*-2)=0 | | K^2-2k-2=0 | | 2e(3x)+4=20 | | 0.5x+3=-x+12 | | a=5u-u | | K^3-3k^2+4k-2=0 | | -25+4h=50.52 | | -1+6y=23 | | 3c-11=34 |